Criticality in self-assessment: Writing learning innovations in forming critical thinking - Harsono, Harsono; Hafsi, Ainur Rofiq; Mukminin, Amirul (Institute of Computer Science (IOCS), 2024)
This qualitative research aims to analyze the implementation of writing learning innovations that emphasize criticality in the self-assessment of class V students at SDI Al Munawwarah, Pamekasan, in the 2022–2023 academic year. Using classroom observation methods, teacher interviews, and document analysis, the research results show that this innovation has a positive impact on the development of students' critical thinking. Students experience an increased ability to convey the quality of their writing objectively, identify strengths and weaknesses in arguments, and carry out in-depth analysis of the structure of their writing. These results demonstrate the importance of integrating criticality in self-assessment into writing instruction at the elementary level, which prepares students to face the increasingly complex demands of the educational world. This research provides practical guidance for educators in developing learning innovations that promote critical thinking. The implication is to increase our understanding of the relationship between self-assessment and critical thinking in elementary education.